Changes in spatial patterns of ammonia dry deposition flux and deposition threshold exceedance according to dispersion model formalism and horizontal resolution. (1st January 2021) - Azouz, Niramson; Beekmann, Matthias; Siour, Guillaume; Cellier, Pierre; Drouet, Jean-Louis
Abstract: Ammonia (NH3 ) emitted into the atmosphere from agricultural sources may affect nearby sensitive ecosystems due to high dry deposition fluxes on vegetation and soil surfaces, contributing to critical load exceedances. Ammonia fluxes near sources are simulated by either short-range atmospheric models or regional models using large grid cell sizes. However, studies are missing on the comparison of the results simulated by these two types of models. This paper presents the effect of model formalism, input factors, especially grid cell size and wind speed and the choice of deposition threshold on the spatial patterns of NH3 dry deposition fluxes and deposition threshold exceedances. We used the Eulerian chemistry-transport model CHIMERE and the Gaussian plume model OPS-ST on two study domains characterised by contrasting land use. We showed that the average annual NH3 dry deposition fluxes over each whole domain are similar for both models. By contrast, NH3 dry deposition fluxes near sources are higher when simulated with OPS-ST that provides analytical solutions that can be sampled with small grid cell sizes ( i.e., from 25 to 1600 m in this study), than with CHIMERE, which uses large grid cell sizes ( i.e., 800 and 1600 m). As a result, the spatial patterns of deposition threshold exceedance were very different between both models. These patterns depend mainly on grid cell size, the input factors and the choice of the deposition threshold value. We show that the model formalism has a relatively small effect on the results and that the differences result mainly from the spatial resolutions to which they can be applied. Simulation results must therefore be interpreted carefully, taking into account the simulation conditions. Graphical abstract: Image 1 Highlights: Patterns of NH3 dry deposition fluxes and exceedances depend on model formalism. Grid cell size affects spatial patterns of dry deposition fluxes and exceedances. Patterns of NH3 emissions affect patterns of dry deposition fluxes and exceedances. Models using large grid cell size miss exceedances in heterogeneous landscapes. Spatial patterns of exceedances change according to the chosen threshold.